2009
DOI: 10.1002/bip.21140
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Val57 amino‐acid residue in the hinge loop of the human cystatin C. Conformational studies of the beta2‐L1‐beta3 segments of wild‐type human cystatin C and its mutants

Abstract: Human cystatin C (HCC) is one of the amyloidogenic proteins to be shown to oligomerize via a three-dimensional domain swapping mechanism. This process precedes the formation of a stable dimer and proceeds particularly easily in the case of the L68Q mutant. According to the proposed mechanism, dimerization of the HCC precedes conformational changes within the beta2 and beta3 strands. In this article, we present conformational studies, using circular dichroism and MD methods, of the beta2-L1-beta3 (His43-Thr72) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Comparison of its sequence with the data for other cystatins available currently in the PDB database, and further analysis in the context of the torsional φ and ψ angle values revealed, that there is the amino acid residue displaying strained conformation, namely valine in position 57, located near the apex of the loop (Rodziewicz-Motowidło et al, 2009; Figure 1A). These tensions may be important for the biological activity of cystatin C, but they may also account for its increased dynamics, especially in the absence of the target protease.…”
Section: The Sequence Of the Hinge Loop As A Gatekeeper Of The Wild-tmentioning
confidence: 99%
“…Comparison of its sequence with the data for other cystatins available currently in the PDB database, and further analysis in the context of the torsional φ and ψ angle values revealed, that there is the amino acid residue displaying strained conformation, namely valine in position 57, located near the apex of the loop (Rodziewicz-Motowidło et al, 2009; Figure 1A). These tensions may be important for the biological activity of cystatin C, but they may also account for its increased dynamics, especially in the absence of the target protease.…”
Section: The Sequence Of the Hinge Loop As A Gatekeeper Of The Wild-tmentioning
confidence: 99%
“…Experimental (Engh et al, 1993;Martin et al, 1995) and theoretical (Dehouck et al, 2003;Rodziewicz-Motowidło et al, 2009) studies revealed that the L1 region of cystatin C is conformationally unstable with the largest component of instability related to the residue V57, located at the apex of the loop. The values of w angles for this residue are not optimal (Rodziewicz-Motowidło et al, 2009), what can explain propensity of the protein to undergo domain swapping.…”
Section: Introductionmentioning
confidence: 97%
“…The values of w angles for this residue are not optimal (Rodziewicz-Motowidło et al, 2009), what can explain propensity of the protein to undergo domain swapping. It agrees with the literature reports linking presence of flexible hinge loops in a protein structure with its ability to swap domains (Ding et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…During domain swapping process, conformational changes concerning the flexible loops as well as β-turns occur (Szymańska et al 2009). The part of the protein that is significantly changed during dimerization is loop L1 which disappears in the dimeric hCC structure (Rodziewicz-Motowidło et al 2009). This region, with its lack of conformational stability, is considered to be the molecular “spring” facilitating the domain exchange (Rodziewicz-Motowidło et al 2009).…”
Section: Discussionmentioning
confidence: 99%